Chronotherapeutic Drug Delivery System - A Detailed Study - D. Nagasamy Venkatesh; N. Arun; S. D. Shanmugakumar (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
The study of circadian clocks and the natural platform’s possible uses for them has led to an increased interest in chronotherapy research. This area of research provides important insights for improving current drug delivery technology. Chronotherapy involves administering drugs in sync with circadian rhythms to target specific sites in the body. Among them pulsatile drug delivery system gains recent attention where the drug is expected to deliver at desired site with right time by offering multiple benefits for the patients. Recently, research has been focused on chronotherapeutics for the disease such as asthma, arthritis, cancer, diabetes, hypertension, hypercholesterlemia, congestive heart failure and stroke. They have been fabricated according to the circadian rhythm of the body to exhibit complete release of drug after the specified lag time, especially for drugs that undergo first pass metabolism by liver and drug requirement during nocturnal dosing. There have been various attempts to develop a therapeutic system that delivers drugs to treat rhythmic diseases based on their occurrence. The ideal chronotherapeutic system should release the drug rapidly and completely after a specific lag time. Researchers have focused on developing chronotherapeutic drug delivery systems using polymer films that are prone to erosion, slippery, or resistant as well as sensory cues systems for delivering drugs. This chapter explores the idea of chronotherapy, problems experienced in its advancement, present methods, and potential uses in medication delivery for treating disorders connected to circadian rhythm.